Human-relevant doses of bisphenol a induce insulin resistance by downregulating Irs1 expression in skeletal muscle through estrogen receptor-α - Zhang-Hong Ke; Yue-Hong Li; Ai-Li Yu; Xue-Fen Cai; Yan-Ying Lin; Shun-He Lin; Chu-Chu Zheng; Chen-Xi Yu; Bei-Hong Zheng; Yan Sun (Ecotoxicology and Environmental Safety, 2025)
Emerging evidence links bisphenol A (BPA) to insulin resistance, but the underlying mechanisms remain unclear. In this study, lactating mother mice and their male offspring post-weaning were exposed to bisphenol A (BPA) via drinking water at human-relevant (2.5 μg/L) and high human-relevant (25 μg/L) concentrations, corresponding to daily intakes of 0.5 and 5 μg/kg body weight, respectively. At 8 weeks of age, male offspring exposed to BPA exhibited evident insulin resistance. RNA sequencing of skeletal muscle identified the insulin signaling pathway as the most significantly disrupted, with Irs1 showing the highest degree of differential expression among key genes involved in glucose metabolism. RT-qPCR and Western blot validation in skeletal muscle, using an expanded sample set, confirmed that Irs1 was uniquely and significantly dysregulated among genes essential for glucose metabolism after exposure to both BPA doses. Furthermore, BPA within and around human-relevant concentrations reduced Irs1 expression and impaired insulin signaling in skeletal muscle in a dose-dependent manner, both in vivo and in C2C12 myotubes. Mechanistic analyses using CUT&Tag, ChIP-qPCR, and luciferase reporter assays demonstrated that BPA disrupts estrogen receptor-α (ERα) binding to the estrogen response element in Irs1 promoter, thereby suppressing Irs1 transcription and antagonizing estrogen’s regulatory effects. This study demonstrates that chronic and early-life exposure of BPA at human-relevant concentrations induces insulin resistance in young adults. BPA around human-relevant concentrations induces insulin resistance by dose-dependently suppressing Irs1 expression in skeletal muscle via interference with ERα binding, highlighting a molecular mechanism of metabolic toxicity and the need for broader exposure control.